The ion-imprinted oyster shell material for targeted removal of Cd(II) from aqueous solution. (15th January 2022) - Wu, Shurong; Liang, Lin; Zhang, Qin; Xiong, Lifeng; Shi, Shuiqin; Chen, Zibin; Lu, Zexiang; Fan, Liwei
Abstract: In order to realize the sustainable utilization of waste oyster shell and develop a targeted removal technology for cadmium. A novel ion-imprinted oyster shell material (IIOS) was prepared by surface imprinting technique. The prepared samples were characterized by scanning electron microscope, Fourier infrared spectrometer, X-ray diffractometer, thermogravimetric analysis and N2 adsorption-desorption. The adsorption performances of IIOS for Cd(II) from aqueous solution were studied by the single factor sequential batch, kinetics, isotherms, selectivity and recycling experiments. The characterization researches showed that IIOS was successfully prepared. The adsorption experiments indicated that the adsorption process reached equilibrium within 240 min; the maximum adsorption capacity was up to 69.1 mg g −1 with the initial Cd(II) concentration of 75 mg L −1 at pH 5; the adsorption process fitted well to the pseudo-second-order model and the Langmuir isotherm model, which revealed the chemisorption characteristic of Cd(II). Moreover, IIOS exhibited a good targeted adsorption of Cd(II) in several binary competition systems owing to the present of these imprinted cavities. The recycling experiment showed that the targeted removal ratio of IIOS for Cd(II) remained above 80% after used six times. The results of this study indicated that it is a promising prospect for waste oyster shell used as IIOS to dispose heavy metals in wastewater. Graphical abstract: Image 1 Highlights: The sustainable utilization of waste oyster shell was realized. A novel IIOS adsorbent was prepared by surface ion-imprinting technique. The adsorption capacity of IIOS on Cd(II) reached 69.1 mg g −1 at pH 5. IIOS had good selectivity toward targeted Cd(II) in the binary competition system. The method can be applied to the production of other waste OS adsorption materials.